2019
DOI: 10.1002/biof.1596
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Quercetin alleviates lipopolysaccharide‐induced inflammatory responses by up‐regulation miR‐124 in human renal tubular epithelial cell line HK‐2

Abstract: Chronic kidney disease (CKD) is a persistent kidney structural and functional disorder. Quercetin is one of active extracted flavonoids and has protective effects. Therefore, we proposed to survey the effect of Quercetin on CKD. HK‐2 cells were preprocessed by Quercetin and then irritated with lipopolysaccharide (LPS). CCK‐8 assay and flow cytometry were utilized to test viability and apoptosis. ELISA assay was utilized to estimate the IL‐6 and TNF‐α secretion. Western blot was performed to examine the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Quercetin is reported to modulate the transport activities of the multidrug-resistance-associated proteins. Moreover, quercetin could not only influence the bioavailability of anticancer and antiviral drugs in vivo but also alleviate endotoxin-stimulated apoptosis and inflammation by up-regulation of relevant micro-RNA [41,42]. Additionally, quercetin could mitigate the intracellular formation of reactive oxygen species (ROS) to reduce the pro-inflammatory response [43].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is reported to modulate the transport activities of the multidrug-resistance-associated proteins. Moreover, quercetin could not only influence the bioavailability of anticancer and antiviral drugs in vivo but also alleviate endotoxin-stimulated apoptosis and inflammation by up-regulation of relevant micro-RNA [41,42]. Additionally, quercetin could mitigate the intracellular formation of reactive oxygen species (ROS) to reduce the pro-inflammatory response [43].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin supplementation had been shown to attenuate D-Galactose-induced renal damage in rats and aflatoxin B1-induced neurotoxicity in mice through the inhibition of oxidative stress (20,21). A recent study also showed that quercetin supplementation could inhibit lipopolysaccharide (LPS)-induced inflammation in a proximal tubular cell line human kidney 2 (HK-2) cells which derived from normal human kidney (22). Yet, whether quercetin may have a protective role in Cu overload-induced nephrotoxicity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a number of miRNAs have been found to directly target MyD88 upon LPS stimulation, including miR-149, hsa-miR-203, miR-214 (Cui et al, 2019;Zheng et al, 2019). Hsa-miR-203 is reported to be involved in the regulation of inflammatory responses in ischemia (Chen et al, 2017). Hsa-miR-203 was also involved in regulating LPS-induced inflammation in macrophage RAW264.7 cells (Wei et al, 2013).…”
Section: Discussionmentioning
confidence: 99%